The pygmy elephant: a myth and a mystery - David Western (Pachyderm)
The paper reviews aspects of the long held debate concerning the existence of the pgymy elephant and notes the author's own observations in the Bayanga Forest in southwestern Central African Republic during a survey in early 1986. The author suggests the persistence of the pygmy elephant myth may be the result of two factors: the tusk development of the forest elephant is more rapid than the savannah or bush elephant, and the belief that such a species exists. However, it appears that two races of elephants do exist in much of the forest areas, but that the two are the forest L. cyclotis and the bush L. africana. This sympatry suggests that there is broader zone of overlap between the ecological conditions favoured by each of the races than generally assumed.